Plan estratégico para la fundación Fucformidm periodo 2019-2023 - Mendoza Cedeño, Dimas Vicente (2019)
The objective of this research work is to propose a strategic plan to improve the administrative management of the foundation, which is based on the strategic direction that the organization wishes to achieve. For this, 3 methodological phases were developed in relation to the subject of study: 1) the internal and external context was diagnosed to know the current situation of the foundation through the interview and survey tools that helped assess the environment inside and outside the company through a questionnaire addressed to the economically active population of the Calceta parish of the urban area, then the EFI, EFE and SWOT matrices were applied, which allowed the search and analysis of positive and negative factors that influenced its management; 2) strategies according to the situational diagnosis of the foundation were defined, that is, the mission, vision and values that gave the organization a distinctive role; very different from that of its competitors thus improving its image and creating FOFADODA strategies to generate new tactics that will help the foundation achieve its purpose; 3) In this phase the operational plan of the foundation was elaborated, within these the Deming circle was carried out and the 5w+1h matrix that is to say the strategies and the objectives that are desired to be achieved, thus obtaining a progressive growth.